COMED (Counting Media) Learning Media to Enhance Learning Outcomes in the Topic of Adding Whole Numbers for Fifth-Grade Elementary School Students - I Made Punia Darmika (MIMBAR PGSD Undiksha, 2026)
Mathematics learning in elementary schools still faces challenges, particularly low student learning outcomes caused by the limited use of engaging and interactive instructional media, especially in the topic of whole number addition. This study aims to analyze the effectiveness of COMED (Counting Media) in improving students’ learning outcomes and mathematical problem-solving skills. This study employed a research and development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of media experts, material experts, education practitioners, and fifth-grade elementary school students. Data were collected through observation, questionnaires, and learning outcome tests using validated instruments. The data were analyzed using Aiken’s formula for validity, percentage-based analysis for practicality, and a t-test for effectiveness after meeting prerequisite tests. The results showed that COMED has a very high level of validity and practicality and is effective in improving students’ learning outcomes. The use of this media helps students understand addition concepts more concretely and systematically. Therefore, COMED can be used as an innovative alternative in mathematics learning. The implications of this study indicate that the use of interactive, manipulative-based learning media can enhance the quality of instruction, promote active student engagement, and assist teachers in presenting mathematical concepts in a more contextual and meaningful way.